Effect of feeding Pleurotus pulmonarius treated empty fruit bunch on nutrient digestibility and milk fatty acid profiles in goats - Zailan, Mohamad Zaihan; Mohamad Salleh, Suraya; Abdullah, Sumaiyah; Yaakub, Halimatun (Springer, 2023)
This study aimed to evaluate the effect of feeding P. pulmonarius-treated empty fruit bunch (FTEFB) on the nutrient intakes, digestibility, milk yield and milk profiles of lactating Saanen goats. A total of nine lactating Saanen goats were used in an incomplete cross-over experimental design. The balanced dietary treatments contain different replacement levels of Napier grass with FTEFB at 0% (0-FT), 25% (25-FT) and 50% (50-FT). The FTEFB contained crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL) at 4.10, 94.6, 70.8 and 19.4% DM, respectively. The replacement of FTEFB in 25-FT did not alter dry matter, NDF, hemicellulose, ADL, ether extract and gross energy intakes when compared to the control fed group (0-FT). The ADF and cellulose intake was higher in 25-FT than in the others (P < 0.001). The digestibility of hemicellulose, cellulose and ADL were not changed in 25-FT compared to the control group (P < 0.05) whereas when 50% FTEFB was incorporated to the diet, intermediate digestibility was decreased significantly (P < 0.05). Milk yield and protein content did not differ between the goat received 25-FT and the control group (P > 0.05). There are no differences in milk fatty profiles between dietary treatments (P > 0.05), except for OCFA. Goat fed with 25-FT had the lowest OCFA (P < 0.01) and significantly reduced the lauric acid concentration (P < 0 .05) when compared to the control group. Thus, replacement of NG in 25-FT does not adversely affect nutrient intake, fibre digestibility (cellulose and hemicellulose), milk yield, milk composition and milk fatty acid profiles. Overall, FTEFB may have potential to be used in the dairy goat diet as a roughage source to replace Napier grass.